The "Talenta" Program (Tahfidz, Language, and Tata Krama) at MIN 3 Bantul: Efforts to Integrate the Curriculum in Shaping a Competitive, Globally Communicative, and Noble-Charactered Qur'ani Generation - Ahmad Agus Salim (Kawakib: Journal of Multidisciplinary Research, 2026)
This study aims to analyze the development and integration of the "Talenta" program (Tahfidz Al-Qur'an, Language, and Tata Krama/Etiquette) at Madrasah Ibtidaiyah Negeri (MIN) 3 Bantul. This program was designed as a curricular innovation to meet contemporary challenges, where madrasah graduates are not only expected to memorize the Al-Qur'an but also to communicate globally and possess strong character. The research method employed is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The results indicate that the integration of the language component (Arabic and English) equips the hafidz and hafidzah (Quran memorizers) with the skills to disseminate knowledge on an international scale. Meanwhile, the etiquette component serves as an ethical foundation, ensuring that the students' spiritual and intellectual intelligence remains rooted in Islamic moral values (akhlakul karimah). The integration of these three components creates a comprehensive, inclusive, and mutually reinforcing competence within the students.